Soulful simplicity : how living with less can lead to so much more - Carver, Courtney (TarcherPerigee, 2017)
Carver's constant striving for "more" was forced to a halt when she was diagnosed with multiple sclerosis. By pursuing practical minimalism, she was able to create more space, more time, less stress-- and even more love in her life. Now she shows readers how to reclaim lightness and ease by getting rid of excess things.